The effect of market concentration audit, audit tenure, and audit fees on audit quality (study on companies listed in the jakarta islamic index (JII) in 2020-2023) - Andriani, Yulia; Sari, Yetri; Ermawati, Liya (ProBisnis : Jurnal Manajemen, 2024)
The purpose of this research is to find out how audit market concentration, audit tenure, and audit fees influence audit quality partially and simultaneously, a study of companies listed on the Jakarta Islamic Index for the 2020-2023 period. Puposive sampling is the method used in this investigation. Using the E-Views 10 program, panel data regression analysis is a display of the data used and secondary data sources from annual financial reports and literature related to the topic for collecting data. Research findings show that partially, audit market concentration has a positive and significant influence on audit quality, audit tenure has a negative and significant influence on audit quality, while audit fees have no influence on audit quality. Simultaneously audit market concentration, audit tenure and audit fees together have a significant influence on audit quality.